The Effect of Motivation and Competence Factor for Improving Patent Examiner Employee Performance - Gawang Sudrajat; Rizal Syarief; Imam Teguh Saptono (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2023)
The human resources who have motivation and competence are success determinants in achieving organizational goals, and those goals will be achieved if the employees demonstrate high performance at work. Several factors that affect performance are motivation and competence. The performance of Patent Examiners at the Directorate General of Intellectual Property DGIP – Ministry of Law and Human Rights (KEMENKUMHAM) tends to decline. The purpose of this study is to analyze the effect of motivation and competence on improving the performance of Patent Examiners in the Directorate of Patent, Layout Design of Integrated Circuit, and Trade Secret – DGIP. There were 92 Patent Examiners as respondents, and the method used in this study was sampling technique using proportional random sampling. The data analysis descriptive analysis of respondents, validity and reliability tests, and Structural Equation Modeling (SEM) analysis with Partial Least Square (PLS). The variables are motivation, competence, and performance. The results of the study show that motivation and competence variables are factors that affect the performance improvement of Patent Examiners in the Directorate of Patent, Layout Design of Integrated Circuit, and Trade Secret – DGIP. The results of this study comprises : 1) motivation influences the performance of Patent Examiners, 2) competence influence on the performance of Patent Examiners, 3) motivation affects the competence of Patent Examiners, 4) competence influences the motivation of Patent Examiners, 5) motivation and competence together affect the performance of Patent Examiners, 6) the main priorities on improving the performance of Patent Examiners are training and quality development of the employees. Keywords: competence, motivation, performance, performance improving, Patent Examiner employee